Asymmeric Formal [3+3]-Cycloaddition Reactions of Nitrones with Electrophilic Vinylcarbene Intermediates - Wang, Xiaochen (2011)
With metal carbene access to dipolar intermediates, 3,6-dihydro-1,2-oxazines are produced in high yields by dirhodium(II) carboxylate catalyzed reactions between nitrones and a β-TBSO-substituted vinyldiazoacetate. High enantiocontrol occurs with catalysis by N-phthaloyl-(S)-(amino acid)-ligated dirhodium carboxylates for [3+3]-cycloaddition reactions with both acyclic and cyclic nitrones.